An Identity Revolution: Meanderings of the Identity, Androgynous Peripheries and Social Networks - Spínola Elías, Yolanda; García Jiménez, María del Mar (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2014)
The development and democratization of Internet, but specially, the prodigality of the social networks arisen in it, put in question the orthodox and even postmodern concepts of identity, fragmenting it, furthermore, at the time they transfer it to the immaterial space of e-identity. Similarly, they have led to the development of new artistic expressions that explore the construction of identity framed in these contexts. However, social networks, regarding to sexual individuality, limit those constructions to the sexual types predefined by the restricted organic binomial man-woman. It is in the Queer Theory and its peripheral identities where we locate the opposition, once again, to the concealment of these differences by conventional-isms. In this work, we tackled an analysis of the concepts and processes of construction in the identity and e-identity in the configuration of the gender. To do this, and as a guide, we established the androgynous and the reflection about this concept in both, on line networks and our physical world. To illustrate it, we tracked the construction and identity of this marginal identity for subsequently; analyze it in a work created for the mass media, a mutable reality to the digital context that is metamorphosed from the instant in which users upload it to the online network for discussion in the forums. The methodology that we have carried out in this research is pure and deductive, in which there has been propitiated an interdisciplinary approach based on a system of a qualitative study. For the temporary disposition of some elements of this paper, we have collected certain historical precedents, announcing the peculiarity of some studies and analysis done before. At the same time, we have gathered information of diverse means, outlining the theories that favor the examination of key elements in the research, especially those regarding to the construction of a sexual identity inside and out of Internet.